Studi Komparatif Hukum Islam dan Hukum Positif Terhadap Praktik Transaksi Jual Beli Dropship Pada E-Commerce - Fikar, Muhammad; Asti, Mulham Jaki; Mustafa, Adriana (Universitas Islam Negeri Alauddin Makassar, 2023)
In this article discusses the Comparative Study of Islamic Law and Positive Law on the Practice of Dropship Buying and Selling Transactions in E-Commerce. The type of research is qualitative library research, with juridical, shari'i and sociological approaches. The source of this research data is the primary approach in the form of the Qur'an, Hadith, quotes from scholars' views and Law Number 19 of 2019 concerning Electronic Information and Transactions. While secondary research data sources are books, journals, and articles. The method of collecting this research data is reading, understanding and citing various literature related to research material. This research data processing technique is analyzing, interpreting, and observing the data used as the object of research. The result of this study is that in the Electronic Information and Transaction Law there is no prohibition to use online transactions using the Dropshipping system, which must be underlined is that a business actor who offers a product through an electronic system must provide clear and correct information related to information on goods traded. While buying and selling online using the Dropshipping system is not prohibited in Islam and can be used in several contracts, such as greeting contracts. The Dropshipping system in buying and selling online has met the requirements and pillars of the validity of buying and selling in Islam.